I-Grabber: Expanding physical reach in a large-display tabletop environment through the use of a virtual grabber - Abednego, M.; Lee, J.-H.; Moon, W.; Park, J.-H. (ITS 2009 - The ACM International Conference on Interactive Tabletops and Surfaces, Proceedings, 2009)
While working on large tabletop interfaces, reaching and manipulating objects beyond the physical reach of a user can be considerably vexing. In order to reach such an object, a user may have to physically move to the object's location. Alternatively, a user could attempt to reach for the object from his/her current location, but the territory of other users may become obstructed as a result. We propose a multi-touch interaction technique which enables users to easily select and manipulate objects that are beyond their physical reach. Our technique provides direct visual feedback to users, which allows them to be aware of their current active location. Using a controllable interactive grabber (I-Grabber) as a virtual hand extension, users can reach and manipulate any object from their current location.